Dietary intake and gastrointestinal integrity in runners undertaking high-intensity exercise in the heat - Etxebarria, N.; Beard, N. A.; Gleeson, M.; Wallett, A.; McDonald, W. A.; Pumpa, K. L.; Pyne, D. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Gastrointestinal disturbances are one of the most common issues for endurance athletes during training and competition in the heat. The relationship between typical dietary intake or nutritional interventions and perturbations in or maintenance of gut integrity is unclear. Twelve well-trained male endurance athletes (peak oxygen consumption = 61.4 ± 7.0 ml·kg-1·min-1) completed two trials in a randomized order in 35 °C (heat) and 21 °C (thermoneutral) conditions and kept a detailed nutritional diary for eight consecutive days between the two trials. The treadmill running trials consisted of 15 min at 60% peak oxygen consumption, 15 min at 75% peak oxygen consumption, followed by 8 × 1-min high-intensity efforts. Venous blood samples were taken at the baseline, at the end of each of the three exercise stages, and 1 hr postexercise to measure gut integrity and the permeability biomarker concentration for intestinal fatty-acid-binding protein, lipopolysaccharide, and lipopolysaccharide-binding protein. The runners self-reported gut symptoms 1 hr postexercise and 3 days postexercise. The heat condition induced large (45-370%) increases in intestinal fatty-acid-binding protein, lipopolysaccharide-binding protein, and lipopolysaccharide concentrations compared with the baseline, but induced mild gastrointestinal symptoms. Carbohydrate and polyunsaturated fat intake 24 hr preexercise were associated with less lipopolysaccharide translocation. Protein, carbohydrate, total fat, and polyunsaturated fat intake (8 days) were positively associated with the percentage increase of intestinal fatty-acid-binding protein in both conditions (range of correlations, 95% confidence interval = .62-.93 [.02, .98]). Typical nutrition intake partly explained increases in biomarkers and the attenuation of symptoms induced by moderate- and high-intensity exercise under both heat and thermoneutral conditions.